The impact of clean lifestyle health promotion on the attitude, motivation, and behaviour of village health cadres - Tetti Solehati; Agus Rahmat; Cecep Eli Kosasih; Nur Oktavia Hidayati (Masyarakat, Kebudayaan dan Politik, 2018)
Pangandaran is a popular tourism destination in West Java, which is annually visited by a high number of foreign and domestic tourists. It has set itself the vision of gaining the title ‘Healthy Village’. However, Pangandaran beach is still fighting the problem of waste, which is easily found along the coast. Thus, disease is mushrooming due to the lack of a Clean Lifestyle (Perilaku Hidup Bersih Sehat/PHBS) and the low awareness of PHBS in the Pangandaran local community. The eﬀorts undertaken to overcome the problem of infectious disease due to the lack of PHBS require great support from various parties such as health service centres and via community participation and the role of cadres, who also manage the Community Health Centres (Pos Pelayanan Terpadu/Posyandu). The study aims to determine the eﬀect of the health promotion of PHBS on the attitude, motivation, and behaviour of the health cadres. The study was quasi-experimental, involving a pre-test and post-test design. The study was conducted in Pangandaran Village, Pangandaran Regency. This research involved the health cadres because they are the closest person to the community and they also run a health program. In addition, they are reliable people when it comes to overcoming health problems in the community. The total population of health cadres in Pangandaran Village amounted to 28 people, via total sampling. The instruments used in this study included a questionnaire, observation sheet, and a checklist. The data analysis used univariate and bivariate analysis. The result showed that the mean score of attitude ranged from 65.11 to 74.71 (p = 0,000), the mean score of motivation was 37.39 to 40.71 (p = 0,000), the mean score of genital hygiene behaviour was 67.96 to 80.61 (p = 0,000) and the mean score of the behaviour of CTPS was significant at 32.25 to 35.71 (p = 0,000). This study found there to be significant diﬀerence in the mean attitude, motivation and behaviour of the health cadres before and after the intervention period.